2021
DOI: 10.1016/j.clinbiomech.2021.105408
|View full text |Cite
|
Sign up to set email alerts
|

Posterior to anterior spinal stiffness measured in a sample of 127 secondary care low back pain patients

Abstract: Background:The sensation of spinal stiffness is a commonly reported symptom among back pain patients, with the clinical assessment of spinal stiffness usually being part of the decision-making process when deciding on providing manual treatment of low back pain. While any relationship between spinal stiffness and low back pain is likely to be multifactorial, prior exploration of this relationship has been overly simplistic (e.g., univariate regression analyses). The purpose of this study was to address this ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…No effect of sex was found in 35 studies (Adnan et al., 2017; Alodaibi et al., 2021; Anderson et al., 2011; Beissner et al., 2012; Beneciuk et al., 2013; Berglund et al., 2015; Brennan et al., 2021; Brooks C, Kennedy S, & Marshall PW, 2012; Burns et al., 2018; Cougot et al., 2015; Feitosa et al., 2016; Fisher et al., 2020; Fritz et al., 2019; Fritz et al., 2013; George & Stryker, 2011; Glattacker et al., 2018; Hügli et al., 2015; Jensen et al., 2013; Kaljic et al., 2018; Murphy et al., 2014; Nava‐Bringas et al., 2016; Neyaz et al., 2019; O’Leary et al., 2020; Oliveira et al., 2019; Pak, Miller, & Cheuy, 2021a; Pietsch et al., 2021; Preuper et al., 2011; Rasmussen‐Barr et al., 2012; Schaller et al., 2017; Stapelfeldt et al., 2011; Van Hooff et al., 2014; Van Koppen et al., 2016; Varela & Van Asselt, 2022; Werneke, Hart, George, Deutscher, & Stratford, 2011; Zheng et al., 2018) while 14 studies demonstrated male sex was associated with better outcomes (Bath & Lovo Grona, 2015; de Heer & Warren, 2016; Farin, 2015; Fehrmann et al., 2022; George & Stryker, 2011; Glattacker et al., 2012; Hadizadeh et al., 2020; Lonsdale et al., 2017; Lutz et al., 2020; Meng et al., 2017; Ozcan Kahraman et al., 2018; Park & Lee, 2016; Wilson et al., 2011; Yağcı et al., 2020). Female sex and better outcomes were demonstrated in seven studies (Beneciuk & George, 2021; Görge et al., 2017; Gregg et al., 2014; Harsted et al., …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No effect of sex was found in 35 studies (Adnan et al., 2017; Alodaibi et al., 2021; Anderson et al., 2011; Beissner et al., 2012; Beneciuk et al., 2013; Berglund et al., 2015; Brennan et al., 2021; Brooks C, Kennedy S, & Marshall PW, 2012; Burns et al., 2018; Cougot et al., 2015; Feitosa et al., 2016; Fisher et al., 2020; Fritz et al., 2019; Fritz et al., 2013; George & Stryker, 2011; Glattacker et al., 2018; Hügli et al., 2015; Jensen et al., 2013; Kaljic et al., 2018; Murphy et al., 2014; Nava‐Bringas et al., 2016; Neyaz et al., 2019; O’Leary et al., 2020; Oliveira et al., 2019; Pak, Miller, & Cheuy, 2021a; Pietsch et al., 2021; Preuper et al., 2011; Rasmussen‐Barr et al., 2012; Schaller et al., 2017; Stapelfeldt et al., 2011; Van Hooff et al., 2014; Van Koppen et al., 2016; Varela & Van Asselt, 2022; Werneke, Hart, George, Deutscher, & Stratford, 2011; Zheng et al., 2018) while 14 studies demonstrated male sex was associated with better outcomes (Bath & Lovo Grona, 2015; de Heer & Warren, 2016; Farin, 2015; Fehrmann et al., 2022; George & Stryker, 2011; Glattacker et al., 2012; Hadizadeh et al., 2020; Lonsdale et al., 2017; Lutz et al., 2020; Meng et al., 2017; Ozcan Kahraman et al., 2018; Park & Lee, 2016; Wilson et al., 2011; Yağcı et al., 2020). Female sex and better outcomes were demonstrated in seven studies (Beneciuk & George, 2021; Görge et al., 2017; Gregg et al., 2014; Harsted et al., …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies evaluated the effect of age on function ( n = 35), pain ( n = 23), and psychological well‐being ( n = 11; Table 3). No effect of age was found in 31 studies (Abu et al., 2017; Anderson et al., 2011; Beissner et al., 2012; Beneciuk et al., 2013; Beneciuk & George, 2021; Berglund et al., 2015; Brennan et al., 2021; Burns et al., 2018; Cougot et al., 2015; Feitosa et al., 2016; Fritz et al., 2019, 2011; George & Stryker, 2011; Glattacker et al., 2012, 2018, Görge et al., 2017; Hügli et al., 2015; Kaljic et al., 2018; Murphy et al., 2014; Nava‐Bringas et al., 2016; Neyaz et al., 2019; O’Leary et al., 2020; Oliveira et al., 2019; Pak et al., 2021; Rajamani et al., 2020; Rasmussen‐Barr et al., 2012; Schaller et al., 2017; Stapelfeldt et al., 2011; Van Hooff et al., 2014; Van Koppen et al., 2016; Walston & McLester, 2020), while 16 studies demonstrated that younger age was associated with better outcomes (Adnan et al., 2017; Alodaibi et al., 2021; Bath & Lovo Grona, 2015; de Heer & Warren, 2016; Fritz et al., 2013; Gregg et al., 2014; Harsted et al., 2021; Heidari et al., 2017; Jensen et al., 2013; Lutz et al., 2020; Preuper et al., 2011; Schwind et al., 2013; Verkerk et al., 2015; Werneke, Hart, George, et al., 2011; Wilson et al., 2011; Yağcı et al., 2020). Older age and better outcomes were demonstrated in four studies (Dhondt et al., 2020; Farin, 2015; Fehrmann et al., 2022; George & Stryker, 2011), one study demonstrate...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations